DETERMINATION OF SPIRITUAL, INTELLECTUAL AND PSYCHOMOTOR INTELLIGENCE ON PERFORMANCE THROUGH COMPETENCE OF SECRETARIAT EMPLOYEES RIAU ISLANDS DPRD, INDONESIA - Wahyu Wahyudin; Chablullah Wibisono; Muammar Khaddafi; Ngaliman; Bambang Satriawan (RADJA PUBLIKA, 2023)
Inspired by research at the Secretariat of the People's Representative Council of the Riau Archipelago Region with the title The Influence of the latent variable Cultural Values on the latent variable Efficiency, which is positive and insignificant, the researcher wants to continue this research with the title Determination of Spiritual, Intellectual and Psychomotor Intelligence on Performance Through the Competence of Secretariat Employees of the Riau Islands DPRD Secretariat. The number of respondents was 188; with the Slovin Formula, a sample of 128 respondents was obtained. Data analysis was carried out using Partial Least Square (PLS). Partial Least Square. The research results are as follows:the positive determination of the Competence variable is significant to the Performance variable, the positive determination of the Intellectual variable is not practical to the Competency variable, the direct positive determination of the Intellectual variable is not essential to the Performance variable, the positive determination of the Psychomotor variable is significant to the Competency variable, the determination of the Intellectual variable is positively not substantial to the Performance variable, the determination of the Intellectual variable is positive and not significant for the Competency variable, the determination of the Spiritual variable is positive and effective for the performance variable, the Competency variable is influenced by the variables of spiritual intelligence, intellectual intelligence and psychomotor intelligence with an interaction of 56.2%, the Performance variable can be explained/controlled by the variables of spiritual intelligence, intellectual intelligence, psychomotor intelligence and competency with their interaction is 63.4%. These findings indicate that Secretariat Staff should have spiritual, intellectual and psychomotor intelligence to improve the competence and performance of the People's Representative Council.